2020
DOI: 10.1177/2473011420975419
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Use in Foot and Ankle Surgery

Abstract: Background: There is a potential role for tranexamic acid (TXA) use in foot and ankle procedures; however, the benefits of this intervention have not been fully elucidated. The purpose of this study was to explore the safety, outcomes, and medical complication profile of the use of intravenous TXA in patients undergoing foot and ankle surgery. Methods: A prospective study with retrospective review of 241 patients undergoing elective and traumatic foot and ankle procedures was performed. One gram of intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Limitations can be attributed to the heterogeneity of included studies, limitation of their design, and risk of unknown bias. For example, the studies by Johns et al 11 and Sadoun et al 19 are observational retrospective studies with no control groups. This can potentially bias their effect on the overall outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations can be attributed to the heterogeneity of included studies, limitation of their design, and risk of unknown bias. For example, the studies by Johns et al 11 and Sadoun et al 19 are observational retrospective studies with no control groups. This can potentially bias their effect on the overall outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of TXA in foot and ankle surgery is relatively rare [ 30 , 31 ]. Currently, few studies have shown that TXA has potential benefits in reducing blood loss and wound complications without increasing the risk of thromboembolic events [ 32 – 34 ], but there is still some controversy [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although extensively studied in other orthopaedic procedures, there lacks a consensus regarding drain use in ankle surgery. 12 , 23 Over the span of our study, tranexamic acid (TXA) became more popular in orthopaedic surgery, reducing the theoretical need for drains because of its ability to decrease blood loss and the risk of blood transfusion. Furthermore, more and more studies in the orthopaedic literature, particularly in primary hip and knee arthroplasty, suggest that drains provide minimal added benefit.…”
Section: Discussionmentioning
confidence: 99%